Geodynamic development of the Ingul megablock of the Ukrainian Shield for geological-geophysical and tectonophysical data. II - O.B. Gintov; S. V. Mychak (Геофизический журнал, 2011)
In the second part of the article (see [Gintov, Mychak, 2011а]) a structure of the Ukrainian Shield (USh) Ingul megablock as a result of about 40 phases of deformation that occurred more than one billion years ago (Neo Archaean-Late Proterozoic) has been described somehow in detail. It is shown that most of the time the megablock experienced compressive stress in shear, and the main phases of extension occurred within 2,05-1,7 billion years ago. The geodynamic interpretation of the materials has been done, according to which the Archaean basement of the USh was made of two microplates - Western and Eastern. In the Archean they were spaced at a considerable distance and developed independently, and on the border of the Archaean and early Proterozoic they came together. The collisional zone between the microplates was the scene of the most intensive processes of tectono-thermal activation, during which massifs of the Novoukrainian, Kirovograd granites and Korsun-Novomirgorodsky pluton of gabbro-anorthosites and rapakivi were formed.